How Would I Simplify (-r+s)(-r-s)?


Answer:
Rules
(-)(-) = +
(-)(+) = -
(+)(-) = -
(+)(+) = +

(-r+s)(-r-s)
Solving the brackets you will get
= (-r)(-r) + (-r)(-s) +(s)(-r) + (s)(-s)

Applying the above mentioned rules
= r^2 + rs - rs - s^2
= r^2 - s^2 >>answer

Or simply you can also apply formula

(a+b)(a-b) = (a^2 -b^2)
(-r+s)(-r-s) = r^2 - s^2


Resolved Questions:
What is the intent of Education?
When a human arrives to the world he/she is like a blank paper. Whatever is written on it he accepts it; it is the writer who does the adjectives in the beginning. So the early stage of erudition for a human being starts from home. So we can easily...

The Sum Of Two Consecutive Integers Is 145. Find The Two Consecutive...
Do not know how to do this. Let two integers be K and k+1 And sum is given 145 Than k+K+1=145 than 2k+1=145 2k=145-1 k=144/2 k=72 than one integer is 72 and other is k+1=72+1=73 I hope you get your...

How Many Ways Can A 5-position Line-up Be Chosen From 8 Players?
The number of combinations of 8 objects taken 5 at a time is ... C[8,5] = 8!/(5!*3!) = (8*7*6)/(3*2*1) = 56. If you play each player's strengths, it is a lot smaller number.